A global database of diversified farming effects on biodiversity and yield - CGIAR Research Program on Water, Land and Ecosystems (2021)
The dataset provides a resource that is being used by researchers and practitioners to easily access information on where diversified farming systems effectively contribute to biodiversity and food production outcomes.